PENGARUH MOTIVASI KERJA, PELATIHAN DAN AUDIT SDM TERHADAP KINERJA PEGAWAI PADA KANTOR AKADEMI TEKNIK DAN KESELAMATAN PENERBANGAN (ATKP) MEDAN - Muhammad Caesar Akbar (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
The formulation of the problem in this study is whether work motivation has a positive and significant effect on performance. Does the training have a positive and significant effect on performance. Does the HR audit have a positive and significant effect on performance. The purpose of this study was to determine and analyze the effect of work motivation on performance. To find out and analyze training on performance. To find out and analyze the human resources audit on performance. The sample in this study amounted to 97 employees. The data analysis technique in this research uses descriptive analysis and quantitative data analysis. The results of this study explain that the variable of work motivation has a positive and significant effect on performance. Training variables have a positive and significant effect on performance. HR audit variables have a positive and significant effect on performance.